Impact of high hydrostatic pressure and thermal treatment on the stability and bioaccessibility of carotenoid and carotenoid esters in astringent persimmon (Diospyros kaki Thunb, var. Rojo Brillante). (September 2019) - Cano, M. Pilar; Gómez-Maqueo, Andrea; Fernández-López, Rebeca; Welti-Chanes, Jorge; García-Cayuela, Tomás
Abstract: The carotenoid and carotenoid ester profile in astringent persimmon ( Diospyros kaki Thunb ., var. Rojo Brillante) was composed by 13 free xanthophylls, 8 hydrocarbon carotenes and 17 carotenoid esters. The stability and biaoccessibility of these carotenoids was determined by an adaptation of the INFOGEST protocol. Results showed that the stability of persimmon carotenoids ranged from 61 to 74%, depending on the digestion phase, being (all- E )-β-cryptoxanthin and (all- E )-antheraxanthin 3-O-palmitate the most stable carotenoids. At the final step of the digestion (oral + gastric + duodenal phase), only traces of (all- E )-antheraxanthin, (all- E )-lutein and (all- E )-β-cryptoxanthin were found in control samples due to the low efficiency of carotenoid micellization, which was affected by the high pectin content naturally present in persimmon tissues. Processing increased the overall carotenoid bioaccessibility to 54% in pressurized samples and to 25% in thermal treated ones. This effect depended on the processing technology as well as on the chemical structure of the carotenoid, being (all- E )-β-cryptoxanthin and (all- E )-β-cryptoxanthin laurate the most bioaccessible carotenoids in pressurized samples and (all- E )-β-cryptoxanthin laurate and (all- E )-antheraxanthin the most bioaccessible ones in pasteurized ones. Graphical abstract: Unlabelled Image Highlights: Bioaccessibility of carotenoids from persimmon is negligible when the fruit is eaten alone (no fats). Stability of carotenoids of persimmon ranged 61–74%, depending the in vitro digestion phase. Pressurization and pasteurization affect positively the persimmon carotenoid bioaccessibility. Light microscopy showed aggregation of pectin-carotenoids, which affected micellarization. Range of carotenoid bioaccessibility ranged to 54% in pressurized samples and to 25% in pasteurized ones.